UPAYA MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN PROPOSAL PENELITIAN TINDAKAN KELAS MELALUI MODEL PELATIHAN PARTISIPATIF DENGAN PENDAMPINGAN INTENSIF - Mediatati, Nani (Universitas Kristen Satya Wacana, 2016)
This study aimed to improve teachers competence at SMP Negeri 1 and 2 Ampel in composing classroomÂ action research (CAR) proposals through participatory training model with intensive assistance. ThisÂ school action research was conducted with the strategy of the cycles starting from problem identification,planning, action, observation, and reflection. Based on the problem identification, teachers had difficultyÂ in composing classroom action research proposal. Action undertaken to overcome the problem in cycle 1Â was applying participatory training model with intensive assistance classically and in cycle 2 wasÂ applying participatory training model with intensive mentoring individually. Data collection techniquesÂ used observation, interview and evaluation. Data analysis used comparative descriptive analysis. TheÂ results showed that there was an increasing of teachersâ competence in preparing classroom actionresearch proposal from cycle 1 to cycle 2. In cycle 1, assessment against the six classroom action researchÂ proposals presented by teachers started from the background, formulation of the problem, researchÂ objectives, the benefits of research, theoretical study, frame of mind, hypothesis, research methods,research schedule, and bibliography, each rated with good (3), sufficient (2), and less (1)criteria. In cycleÂ 2, the assessment of the six proposals presented by teachers was all rated by good criteria. ObservationÂ towards the training process showed that the teachers had seriousness, willingness, and high reactivity toÂ develop classroom action research proposals. The active participation of teachers in the process ofÂ intensive training and mentoring both in classical and individuals supported the success of this schoolÂ action research that the teachers could prepare classroom action research proposals with good criteria.